The Religious Right's Compassionate Steward and Conservationist: The Lost Philosophies of Pat Robertson - Pogue, Neall (Environmental ethics, 2016)
Current scholars use the anti-environmental rhetoric of Pat Robertson to argue that the politically important religious right movement, which he co-founded and led, has always ignored and/or opposed nature protection efforts. During the movement's initial years, from the late 1970s to 1989, however, Robertson encouraged eco-friendly philosophies best described as conservation and Christian compassionate stewardship. He publically endorsed these views through publishing, speaking out at politically charged venues, and by ignoring religious right political allies who favored economic growth over environmental protection. During this early period, Robertson was not an anti-environmentalist but instead promoted thoughtful and nuanced eco-friendly philosophies. Furthermore, it is likely that the larger religious right community shared these views. This examination of Robertson's eco-friendly positions lays a foundation for future scholarship on the religious right's relationship with environmentalism.